2012
DOI: 10.1161/jaha.111.000422
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima‐Media Thickness Progression in HIV‐Infected Adults Occurs Preferentially at the Carotid Bifurcation and Is Predicted by Inflammation

Abstract: Background Shear stress gradients and inflammation have been causally associated with atherosclerosis development in carotid bifurcation regions. The mechanism underlying higher levels of carotid intima‐media thickness observed among HIV‐infected individuals remains unknown. Methods and Results We measured carotid intima‐media thickness progression and development of plaque in the common carotid, bifurcation region, and internal carotid artery in 300 HIV‐infected persons and 47 controls. The median duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 52 publications
7
79
2
3
Order By: Relevance
“…PWV indicate pulse wave velocity; IMT, intima media thickness; TC, total cholesterol; HDL-C, high density lipoprotein cholesterol; LDL-C, low density lipoprotein cholesterol; TG, triglyceride; CRP, C reactive protein; IL-6, interleukin 6; ICAM, intracellular adhesion molecule; VCAM vascular cell adhesion molecule. agreement with that of Currier et al, who did not detect subclinical atherosclerosis in the HIV infected population [43], but in contrast to several studies that indicate a higher IMT in HIV infected individuals [12,44,45]. According to Hsue et al, this may be explained by the fact that we measured the IMT in the common carotid artery, while the differences seen by them and Lorenz et al, were mainly in the carotid bifurcation region [45] where there is low endothelial shear stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PWV indicate pulse wave velocity; IMT, intima media thickness; TC, total cholesterol; HDL-C, high density lipoprotein cholesterol; LDL-C, low density lipoprotein cholesterol; TG, triglyceride; CRP, C reactive protein; IL-6, interleukin 6; ICAM, intracellular adhesion molecule; VCAM vascular cell adhesion molecule. agreement with that of Currier et al, who did not detect subclinical atherosclerosis in the HIV infected population [43], but in contrast to several studies that indicate a higher IMT in HIV infected individuals [12,44,45]. According to Hsue et al, this may be explained by the fact that we measured the IMT in the common carotid artery, while the differences seen by them and Lorenz et al, were mainly in the carotid bifurcation region [45] where there is low endothelial shear stress.…”
Section: Discussionsupporting
confidence: 91%
“…agreement with that of Currier et al, who did not detect subclinical atherosclerosis in the HIV infected population [43], but in contrast to several studies that indicate a higher IMT in HIV infected individuals [12,44,45]. According to Hsue et al, this may be explained by the fact that we measured the IMT in the common carotid artery, while the differences seen by them and Lorenz et al, were mainly in the carotid bifurcation region [45] where there is low endothelial shear stress. Low endothelial shear stress may enhance the effect of chronic inflammation which may lead to the increased expression of vascular adhesion molecules and proinflammatory cytokines [46], which may explain the endothelial activation seen in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Soluble markers of monocyte and macrophage activation have been linked to both HIV disease progression and serious non-AIDS events [5,12**,17,18,19,38**,39,40,41*]. More recently, higher CD16 expression was found to be an independent predictor of atherosclerosis progression [42], highlighting the need to assess monocyte phenotypes as potential targets of therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown persistently increased T cell activation and inflammation in chronically treated patients [5,13,18,22-25,31,35,36*,37**,38**,39,41*,44-46]. The potential causes include residual HIV replication, gut mucosal injury and subsequent microbial translocation, tissue fibrosis, co-infections such as cytomegalovirus and hepatitis C virus, and homeostatic drive [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, coronary atherosclerotic lesions in HIV-infected patients are often unstable and more prone to rupture, resulting in a 1.5-twofold higher incidence of acute coronary syndrome and myocardial infarction. [8][9][10][11] Expectedly, these pathologic changes leave HIV-infected patients at risk for vascular injury, accelerated atherosclerosis, 12 and ultimately disproportionate cardiovascular mortality. 13 Finally, despite widespread use of ART, we are just now appreciating the burden of inflammation and resulting cardiovascular damage which threatens patient survival.…”
mentioning
confidence: 99%